Explore BrainMass

Explore BrainMass

    Solving Logarithmic Equations

    Not what you're looking for? Search our solutions OR ask your own Custom question.

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    A) Solve the equation:
    log3 (2 - 3x) = log9 (6x2 - 19x + 2)

    b) Prove that if a^x = b^y = (ab)^xy, then:
    x + y = 1.

    See the attached file.

    © BrainMass Inc. brainmass.com March 4, 2021, 7:52 pm ad1c9bdddf
    https://brainmass.com/math/basic-algebra/solving-proving-logarithmic-equations-128478

    Attachments

    Solution Preview

    Please see the attached file for the complete solution.

    a) Solve the equation:
    log3 (2 - 3x) = log9 (6x2 - 19x + 2)
    Solution:

    We know that logxy = log y / log x [Base rule]

    Then:

    log3(2 - 3x) = log9(6x^2 - 19x +2)

    log(2 - 3x) / log 3 = log(6x^2 - 19x +2) / log ...

    Solution Summary

    A logarithmic equation is solved in the solution.

    $2.49

    ADVERTISEMENT